The wide-awake princess - Baker, E. D. (New York : Bloomsbury, 2010)
Annie, younger sister of the princess who would be known as Sleeping Beauty, is immune to magic and stays awake when the rest of the castle falls into an enchanted sleep, then sets out to find a way to break the spell.
School Library Journal, June 2010.
Horn Book, October 2010.
Kirkus Review, April 2010.
Library Media Connection, August 2010.
School Library Journal.
Horn Book.
Keywords: Fairy tales; Princesses -- Juvenile fiction; Beauty, Personal -- Juvenile fiction; Magic -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Princesses -- Fiction; Beauty, Personal -- Fiction; Magic -- Fiction; Characters in literature -- Fiction; Fairy tales; Fantasy; Princesses -- Fiction; Personal appearance -- Fiction; Magic -- Fiction; Characters and characteristics in literature -- Fiction; Fairy tales; Fantasy fiction; Fairy tales; Princesses -- Fiction; Beauty, Personal -- Fiction; Magic -- Fiction; Characters in literature -- Fiction; Fairy tales; Fantasy fiction